Monocytes and Macrophages, Targets of Severe Acute Respiratory Syndrome Coronavirus 2: The Clue for Coronavirus Disease 2019 Immunoparalysis. (25th January 2021) - Boumaza, Asma; Gay, Laetitia; Mezouar, Soraya; Bestion, Eloïne; Diallo, Aïssatou Bailo; Michel, Moise; Desnues, Benoit; Raoult, Didier; La Scola, Bernard; Halfon, Philippe; Vitte, Joana; Olive, Daniel; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) clinical expression is pleiomorphic, severity is related to age and comorbidities such as diabetes and hypertension, and pathophysiology involves aberrant immune activation and lymphopenia. We wondered if the myeloid compartment was affected during COVID-19 and if monocytes and macrophages could be infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: Monocytes and monocyte-derived macrophages (MDMs) from COVID-19 patients and controls were infected with SARS-CoV-2 and extensively investigated with immunofluorescence, viral RNA extraction and quantification, and total RNA extraction followed by reverse-transcription quantitative polymerase chain reaction using specific primers, supernatant cytokines (interleukins 6, 10, and 1β; interferon-β; transforming growth factor–β1, and tumor necrosis factor–α), and flow cytometry. The effect of M1- vs M2-type or no polarization prior to infection was assessed. Results: SARS-CoV-2 efficiently infected monocytes and MDMs, but their infection is abortive. Infection was associated with immunoregulatory cytokines secretion and the induction of a macrophagic specific transcriptional program characterized by the upregulation of M2-type molecules. In vitro polarization did not account for permissivity to SARS-CoV-2, since M1- and M2-type MDMs were similarly infected. In COVID-19 patients, monocytes exhibited lower counts affecting all subsets, decreased expression of HLA-DR, and increased expression of CD163, irrespective of severity. Conclusions: SARS-CoV-2 drives monocytes and macrophages to induce host immunoparalysis for the benefit of COVID-19 progression. SARS-CoV-2 infection of macrophages induces a specific M2 transcriptional program. In Covid-19 patients, monocyte subsets were decreased associated with up-expression of the immunoregulatory molecule CD163 suggesting that SARS-CoV-2 drives immune system for the benefit of Covid-19 disease progression.